Caveolin as a potential drug target for cardiovascular protection - Sellers, Stephanie L.; Trane, Andy; Bernatchez, Pascal N. (Frontiers in Physiology, 2012)
Caveolae and caveolin are key players in a number of disease processes. Current research indicates that caveolins play a significant role in cardiovascular disease and dysfunction. The far-reaching roles of caveolins in disease and dysfunction make them particularly notable therapeutic targets. In particular, caveolin-1 and caveolin-3 have been identified as potential regulators of vascular dysfunction and heart disease, and might even confer cardiac protection in certain settings. Such a central role in vascular health therefore makes manipulation of caveolin-1/3 function or expression levels clear therapeutic targets in a variety of cardiovascular related disease states. Here, we highlight the role of caveolin-1 and -3 in cardiovascular health and explore the potential of caveolin-1 and caveolin-3 derived experimental therapeutics.